The Influence of the Bi Rate, Inflation, and Gross Domestic Product on Bond Yields - Mahirun, Mahirun; Fuadah, Syifaul; Jannati, Arih (KnE Social Sciences, 2024)
The objective of this study is to examine and analyze the impact of macroeconomic variables that we suspect affect bond yields including BI rate, inflation, gross domestic product. The population in our study is banking companies in the period 2017 - 2020, and the analytical tool used is multiple linear regression to test the effect of independent variables on the dependent variable. Analysis of the main test on 50 samples revealed that the BI rate and inflation exhibit a positive and statistically significant impact on bond yields, whereas the gross domestic product variable, while significant, exerts a negative influence. Keywords: BI rate, inflation, gross domestic product, bond yield, banking